Pengaruh Corporate Governance pada Konservatisma Akuntansi Perusahaan Manufaktur di Bursa Efek Indonesia - Fiasari, Natalia (E-Jurnal Akuntansi, 2014)
800x600 Accounting conservatism is the precautionary principle to the recognition and profit recognition. Accounting conservatism can be said to be anticipating loss than profit. Corporate governance is a system to manage the company in order to accommodate the interests of stakeholders. Both the poor application of corporate governance will affect the stakeholders' interests are protected or not. Accounting conservatism is a very useful tool for corporate governance mechanisms in carrying out their functions as decision makers and those who monitor management. This research is aiming to see the correlation among corporate governance in accounting conservatism. This research as carried out at manufacture company in the Indonesia Stock Exchange in 2011–2012 period. Sample selection do by purposive sampling method and obtained 79 companies in criteria accordingly. This study used data anayisis and simple linear regression. To determine the corporate governance proxy used factor analysis. The result showed that the effect of corporate governance is positive significant in accounting conservatism with accrual and market to book value method . Normal 0 false false false EN-US X-NONE X-NONE
Keywords: accounting conservatism, corporate governance, accrual and market to book ratio.